Automatic information retrieval through text-mining - Viana, Hugo Henrique Amorim (2013)
The dissertation presented for obtaining the Master’s Degree in Electrical Engineering and Computer Science, at Universidade Nova de Lisboa, Faculdade de Ciências e Tecnologia